Kepastian Hukum Penerapan Online Single Submission Risk-Based Approach (OSS RBA) Sebagai Sistem Perizinan Berusaha Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Widana, Ketut (Sekolah Tinggi Ilmu Hukum Graha Kirana, 2024)
Online Single Submission Risk Based Approach (OSS RBA) is basically a form of updating business licensing services through the Online Single Submission (OSS) system. However, the existence of the OSS RBA is starting to be doubted in line with the Constitutional Court Decision Number 91/PUU-XVIII/2020 concerning Formal Review of the Job Creation Law against the 1945 Constitution which could have implications for legal uncertainty. This research uses a normative legal research method, namely by using secondary data consisting of primary, secondary and tertiary legal materials, then analyzed using qualitative descriptive analysis. The presence of the PP OSS RBA Job Creation Perpu is still valid and has legal certainty. These provisions are contained in Article 184 of the Job Creation Perpu which explains that all implementing regulations in the Job Creation law are still valid as long as they do not conflict with the Job Creation Perpu. We hope that adjustments between the Job Creation Perpu and PP OSS RBA need to be carried out in a careful and careful manner, in this should focus on harmony and consistency within the broader legal framework. So that we can maintain the continuity of applicable legislation, while ensuring the business licensing process remains in accordance with applicable legal principles.